Modern marketing concepts as the basis for formation and increase of the attractiveness of cities and territories. - Гавриш, Ірина Іванівна; Буднікевич, Ірина Михайлівна (Baltic Journal of Economic Studies, 2017)
Instruments of formation and increase of attractiveness of the territory within the framework of modern marketing conceptions, the role of marketing complex elements in shaping the attractiveness of the territories are examined, separate economical categories, forming notional instrument of the attractiveness of the territories are specified and proposals concerning the directions of marketing efforts are formulated. Methodology. Theoretical and methodological basis of the research is the work of scientists on marketing problems of the city, theory of I. Budnikevych, identifying the characteristics of territorial marketing (municipal, city marketing) within industrial, commodity, sale, classical, social-ethic and partnership conceptions. The authors used the combination of following methods in the process of scientific investigation: method of generalization and scientific abstraction – for concrete definition of notional-categorial apparatus; analytical monographic method – to represent scientific thoughts on the directions of marketing instruments application in the processes of territorial attractiveness management; comparative analysis – to find out the peculiarities of marketing instruments and methods use within the limits of different concepts and at different stages of territorial development. Practical value. It was defined that territorial marketing system allows to expand traditional approaches to the policy of regional and local authority’s attractiveness, supplementing them with modern components and characteristics. Nowadays, the instruments of situational conceptions are still actively applied by homeland and foreign territorial marketing practice, sale conception in particular, which stipulates the direction of territorial authorities’ activity to satisfy territorial needs. The instruments of modern territorial marketing conceptions allow to form and increase the attractiveness of territories for defined target audiences. Using the instruments of municipal marketing social-ethic conception one can focus target audiences’ attention on social, ecological and economical territorial attractiveness ensuring stable territorial development. Territorial marketing within the framework of partnership conceptions as the philosophy of territorial (region, city) functioning based on the formation, support and development of mutually beneficial long-term relations between the participants of interaction will create new common values, obtaining and sharing advantages of this activity. The development of the relations between territory and its target audiences defines and forms the basis of the environment to make decisions as to the habitation, visiting, conducting business, investment etc., i. e. forms specific territory’s (country, region, city, settlement) attractiveness. Novelty. On the basis of this research the authors proposed to consider marketing approach to territorial (regional, urban) attractiveness as a transition to long-term development in the field of systematic management on the basis of consumers’ demands orientation and partnership, clear definition of target audience and its demands, flexible regional policy, applying both traditional and non-traditional instruments to form, improve, support and, sometimes, decrease the attractiveness of territory with demarketing means. Conclusions. It has been determined, that according to marketing approach, the attractiveness of the territory is – the ideas total about properties and features, factors and conditions, limits and possibilities, means and instruments, providing satisfaction and the perspective of increase of target audiences’ needs while they choose a proper region for activity and organize their loyalty towards the territory (region, city). Marketing policy of the attractiveness of territories is proposed as a complex of measures aimed at attracting target audience’s attention, it’s being worked out and realized by territorial bodies (members of the community take active part) and it is the element of territorial programs and development strategy. Marketing efforts should be fixed on the increase of territorial attractiveness not only for the inhabitants but for other target groups – tourists, visitors, investors, population and entrepreneurs from other cities, subjects of regional, national and international levels. Investment, settlement, social, business, innovation, tourist and educational attractiveness will favour long-term paretnership formation with target audiences. Marketing instruments ensure long-term relations, helping to increase an transform territorial image, provide loyalty of all the subjects, objects and contact territorial audience, and they are one of the most complex and effective mechanisms of formation and increase of the attractiveness of territories, their promotion in internal and external social-economic environment.
Modern marketing concepts as the basis for formation and increase of the attractiveness of cities and territories.
Keywords: marketing conceptions, city marketing, municipal marketing, classical marketing conception, socialethic marketing conception, relationship conception, marketing techniques, marketing influence, attractiveness of territories, marketing approach, marketing policy of attractiveness